2017
DOI: 10.1016/j.atmosenv.2016.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reaction rates of ozone in water infusions of wheat, beech, oak and pine leaves of different ages

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 69 publications
4
39
0
Order By: Relevance
“…Important nonstomatal deposition pathways over vegetation include surface‐mediated chemical destruction on soil and leaf cuticles. Cuticular uptake occurs when ozone reacts with compounds on the leaf surface (Potier et al, ; Sun, Moravek, Trebs, et al, ). Water films from dew and rain may enhance cuticular uptake, but there is variability in the response to wetness observed in the field and laboratory (Altimir et al, ; Cape et al, ; Fuentes et al, ; Grantz et al, , ; Lamaud et al, ; Massman, ; Pöschl & Shiraiwa, ; Potier et al, ; Turnipseed et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important nonstomatal deposition pathways over vegetation include surface‐mediated chemical destruction on soil and leaf cuticles. Cuticular uptake occurs when ozone reacts with compounds on the leaf surface (Potier et al, ; Sun, Moravek, Trebs, et al, ). Water films from dew and rain may enhance cuticular uptake, but there is variability in the response to wetness observed in the field and laboratory (Altimir et al, ; Cape et al, ; Fuentes et al, ; Grantz et al, , ; Lamaud et al, ; Massman, ; Pöschl & Shiraiwa, ; Potier et al, ; Turnipseed et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Water films from dew and rain may enhance cuticular uptake, but there is variability in the response to wetness observed in the field and laboratory (Altimir et al, 2006;Cape et al, 2009;Grantz et al, 1995Grantz et al, , 1997Lamaud et al, 2002;Massman, 2004;Pöschl & Shiraiwa, 2015;Potier et al, 2015;Turnipseed et al, 2009;Zhang et al, 2002). Previous work suggests that ozone dry deposition to rain-wet leaves may be low because rain cleanses the leaf surface of substances reactive with ozone (Finkelstein et al, 2000;Potier et al, 2017); this may explain some of the observed variability in the response to wetness. Microscopic water films that form when hygroscopic particles on leaf cuticles promote leaf-level increases in moisture may also enhance cuticular deposition (Burkhardt & Hunsche, 2013;Sun, Moravek, Trebs, et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…temperature acclimation). An advancement of these efforts includes harmonizing R s with that computed by land surface models (Ran et al, 2017a;Val Martin et al, 2014), which calculate R s by coupled photosynthesisstomatal conductance (A n -g s ) models (Ball et al, 1987;Collatz et al, 1991Collatz et al, , 1992. Such coupling should theoretically give a more realistic account of ecophysiological controls on R s .…”
Section: Introductionmentioning
confidence: 99%
“…R g ) or simply scaled with leaf area index (LAI) (e.g. R cut ) (Simpson et al, 2012;Wang et al, 1998;Wesely, 1989), while some of the parameterizations (Zhang et al, 2003;Zhou et al, 2017) incorporate the observation of enhanced cuticular O 3 uptake under leaf surface wetness (Altimir et al, 2006;Potier et al, 2015Potier et al, , 2017Sun et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of precipitation on ozone through wet scavenging is negligible. Potier et al, 2017) but the mechanism for this enhancement is uncertain and is not included in the model.…”
Section: Relationship To Cloud Cover and Precipitationmentioning
confidence: 99%